The absence of Investigative Teaching in current Biology teacher training curricula (Research, Society and Development, 2025)
Increasingly, authors have defended the need for a renewal in scientific education. In this meantime, a renewal in teacher training becomes crucial. For this reality to be comprehensive and universal, its presence in curriculum is required. The objective of this article is to discuss the presence of Investigative Teaching (EI) in the construction of the curricula of initial teacher training in Biological Sciences of three public Higher Education Institutions of Teacher Training, in the State of Piauí, and presents how EI is contemplated in these documents, and also in the guiding curriculum of Basic Education and Brazilian Teacher Training. Thus, this work is the result of qualitative research, part of the Doctoral Thesis work of the Postgraduate Program in Science Teaching at the Federal University of Mato Grosso do Sul. The data was obtained through Document Analysis of the Pedagogical Projects of Science Courses. three Public Teacher Training Institutions in the state of Piauí and national educational documents in the search for elements that deal with Investigative Teaching in teacher training curricula. The data was interpreted in light of Eni Orlandi's Discourse Analysis. We consider that the national guidelines, despite the discourse of renewal, have provided little scope for intellectual freedom in education recommended by the EI. The way in which it was implemented also generated many divergences and suffering in teacher training curricula.